Preparation and Characterization of Flexible and Stretchable Polymeric Magnet - Basuli, U.; Kim, S.; Gent, A.N.; Nah, C. (Asian Journal of Chemistry, 2013)
Nano iron oxides (Fe3O4) with a controlled particle size were synthesized using a wet chemical method. A series of nanocomposites based on these magnetic nanoparticles and liquid silicone rubber were prepared using a direct mixing technique. A commercial grade of barium ferrite (BaFe12O19) nanoparticles with a narrow size distribution was used for the preparation of liquid silicone rubber (LSR)/BaFe12O19 nanocomposites. Transmission electron microscopy of the resulting nanocomposite (LSR/Fe3O4 or LSR/BaFe12O19) showed that the nanoparticles were dispersed homogeneously in the liquid silicone rubber matrix. The magnetic nanoparticles were oriented randomly in the polymeric matrix. On the other hand, when these nanocomposites were placed in a magnetic field, the nanoparticles were generally aligned along the longitudinal direction inside the matrix. The magnetic-field induced orientation of magnetic nanoparticles was observed within the polymer matrix. The super-paramagnetic property of the nanocomposite was examined by vibrating sample magnetometer analysis.